Increasing efficiency for reducing elective surgery waiting times: a multi-interventions approach. (30th September 2020) - Quercioli, C; Carta, G A; Cevenini, G; Messina, G; Nante, N; Becattini, G; Sancasciani, S
Abstract: Background: Elective surgery long waiting times are a common problem in publicly funded health systems. They have been tackled allocating additional resources or using existing resources more efficiently but results are patchy. We studied the effectiveness of a multi-interventions project based on the reorganization of existing capacity. Methods: In a district general hospital (Siena's Province, Italy) with 150 beds, 4 elective surgery operating rooms (ORs) opened 6 hours/day 5 days/week (surgery specialties: general surgery, orthopedics, gynecology and urology) in October 2018 a project for reducing surgery waiting times was implemented based on 3 key points: i) separation of the Day Surgery (DS) flow from that of the ordinary activity; ii) increase of available operating time through reorganization of personnel: 30 additional hours/week were made available; iii) allocation of operating sessions flexibly in proportion to the waiting list: the made-available hours were redistributed through an algorithm able to estimate the optimal allocation of surgical time blocks to minimize the length of waiting lists, taking account of the interventions priority class. The waiting time of the out from 1/10/2019 to 31/12/2019 (N = 635) was compared with that of the interventions carried out from 1/10/2018 to 31/12/2018 (N = 634) using t-test. Results: Waiting times for non-urgent cases (that can be operated beyond 30 days) were significantly reduced for all specialties (p < 0.01) except urology. For general surgery, orthopedics and gynecology, DS interventions' mean waiting time decreases from 198 to 100 days (-50%) that one of ordinary interventions from 213 to 134 days (-37%). Waiting time for urgent cases (to be operated within 30 days) was also reduced. Conclusions: A multi-interventions project based on using existing capacity (personnel and structures) more efficiently and improving planning methodologies resulted to be strongly effective in reducing waiting times for elective surgery. Key messages: To effectively reduce surgical waiting times, a strategy is needed that involve the entire process: from surgical planning, to staff and structures organization. The flexible OR time allocation on the base of the waiting list is a key point to improve surgery planning and reduce waiting list.